13C chemical shift tensors in MOF α‐Mg3(HCOO)6: Which component is more sensitive to host‐guest interaction?. (13th December 2019) - Xu, Jun; Terskikh, Victor V.; Chu, Yueying; Zheng, Anmin; Huang, Yining
Abstract: Metal–organic frameworks (MOFs) are a class of important porous materials with many current and potential applications. Their applications almost always involve the interaction between host framework and guest species. Therefore, understanding of host–guest interaction in MOF systems is fundamentally important. Solid‐state NMR spectroscopy is an excellent technique for investigating host–guest interaction as it provides information complementary to that obtained from X‐ray diffraction. In this work, using MOF α ‐Mg3 (HCOO)6 as an example, we demonstrated that 13 C chemical shift tensor of organic linker can be utilized to probe the host–guest interaction in MOFs. Obtaining 13 C chemical shift tensor components ( δ 11, δ 22, and δ 33, where δ 11 ≥ δ 22 ≥ δ 33 ) in this MOF is particularly challenging as there are six coordinatively equivalent but crystallographically non‐equivalent carbons in the unit cell with very similar local coordination environment. Two‐dimensional magic‐angle‐turning experiments were employed to measure the 13 C chemical shift tensors of each individual crystallographically non‐equivalent carbon in three microporous α ‐Mg3 (HCOO)6 samples with different guest species. The results indicate that the δ 22 component (with its direction approximately being co‐planar with the formate anion and perpendicular to the C−H bond) is more sensitive to the adsorbate molecules inside the MOF channel due to the weak C−H···O hydrogen bonding or the ring current effect of benzene. The 13 C isotropic chemical shift, on the other hand, seems much less sensitive to the subtle changes in the local environment around formate linker induced by adsorption. The approach described in this study may be used in future studies on host–guest interaction within MOFs. Abstract : Two‐dimensional magic‐angle turning NMR experiments were performed to measure the 13 C chemical shift tensor components of each individual formate carbon in three microporous α ‐Mg3 (HCOO)6 samples. The results indicate the δ 22 component of 13 C chemical shift tensor is more sensitive to the adsorption of guest species compared to the isotropic chemical shift, providing insights on the host–guest interaction such as hydrogen bonding within metal–organic frameworks.